Legal Protection Of Internists In The Administration Of Alprazolam Without A Prescription - Rudi Mahruzar; Kusbianto Kusbianto; Ariman Sitompul (International Asia Of Law and Money Laundering, 2023)
This study was conducted with the aim to determine how the governing provisions related to psychotropics and how the application of criminal sanctions for dealers, users and owners, users of psychotropics according to Law No. 5 of 1997. By using normative juridical research methods, it is concluded: 1. At first the provisions of the regulation of psychotropics in Law No. 5 of 1997 include: psychotropics Group I, Group II, Glongan III, and Group IV in accordance with the lapiran in legislation and after there is a new law regulating narcotics namely Law No. 35 of 2009, then psychotropics for Group I and Group II have already become a Narcotics Crime Group I. 2. The application of criminal sanctions in Law No. 5 of 1997 on psychotropics in accordance with Article 59 can be dropped the main crime, namely the main crime and additional crimes. The main crimes include imprisonment of 20 years, life imprisonment and death while additional crimes for additional crimes in the form of revocation of business licenses are imposed on corporations and foreigners in accordance with the qualifications of prohibited acts, namely, possession, carrying, circulating, using, psychotropic substances in receiving Alprazolam without a prescription, some important things that must be considered are ensuring strict documentation regarding patient demand and monitoring, ensuring the quality of care and treatment received by patients in accordance with quality standards, ensuring that patients understand their rights and responsibilities in receiving treatment, and protecting patients' rights from actions that are not in accordance with medical law and ethics. This is all aimed at ensuring legal protection for patients in the receipt of quality treatment and in accordance with applicable standards.